(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
This article examines the effects of foliar feeding of cotton with liquid nitrogen fertilizers on the growth and development of cotton. Physiologically active substances play a very important role in the care of crops in agriculture, in increasing seed germination and germination capacity, in improving plant growth and development, in increasing resistance to drought, salt, disease and pests. they have a positive effect on the plant.